Patterns of summer ichthyoplankton distribution, including invasive species, in the Bering and Chukchi Seas - Kim, Sung Hoon; Son, Wuju; Yoo, Jaeill; Cho, Kyoung-Ho; Park, Taewook; Yang, Eun Jin; Kang, Sung-Ho; La, Hyoung Sul (Frontiers in Marine Science, 2024)
A multidisciplinary survey was carried out in the Pacific Arctic and sub-Arctic regions of the North Pacific Ocean on the Korean icebreaking research vessel Araon. During this survey, ichthyoplankton fishes in the Pacific Arctic and sub-Arctic region ranged from the Bering Sea to the northern Chukchi Shelf in summer. The most dominant species was Gadus chalcogrammus, followed by Pleuronectes quadrituberculatus and Boreogadus saida. Gadus chalcogrammus and P. quadrituberculatus were particularly abundant near the Bering Sea and Bering Strait, whereas B. saida was dominant in the Chukchi Sea. Hierarchical cluster analysis revealed four distinct ichthyoplankton communities in Pacific Arctic and sub-Arctic regions based on geographical regions. However, Eleginus gracilis, which was previously known to be seen between latitudes 66.5°N and 69.5°N, was found above 70°N, suggesting that its distribution extends further north. Furthermore, we noticed that Benthosema glaciale, which is usually found in the Atlantic sector of Arctic Ocean, was observed in the northern Chukchi Sea. In addition to these unusual species distributions, several species that are mainly observed in coastal areas are observed in the Chukchi Sea region. The observed influx of various uncommon fish species into the Chukchi Sea can be attributed to multiple factors, including freshwater inflow from the East Siberian Sea and the intrusion of warm Atlantic and Pacific waters, which are strongly affected by global warming. Consequently, it is imperative to conduct rigorous monitoring of the Pacific Arctic region, with a particular focus on the Chukchi Sea, to better understand the implications of global warming.